A circulating electrolyte for a high performance carbon-based dye-sensitized solar cell. Issue 40 (5th May 2017) - Gu, Shuai; Bi, Enbing; Fu, Bitian; Dodbiba, Gjergj; Fujita, Toyohisa; Wilkinson, David P.; Wei, Yuezhou; Fang, Baizeng
Abstract : Novel Pt-free dye-sensitized solar cells with a circulating electrolyte demonstrate much better photovoltaic performance than those with a stationary one. Abstract : An innovative Pt-free counter electrode was developed through which an electrolyte solution could be circulated in dye-sensitized solar cells (DSCs) to facilitate mass transfer, resulting in greatly suppressed charge recombination and a considerably enhanced electron lifetime, and accordingly much higher power conversion efficiency than a DSC with a stationary electrolyte.